Comparative Behavioral Phenotypes of Fmr1 KO, Fxr2 Het, and Fmr1 KO/Fxr2 Het Mice - Saré, Rachel Michelle (Brain Sci, 2019)
Fragile X syndrome (FXS) is caused by silencing of the FMR1 gene leading to loss of the protein product fragile X mental retardation protein (FMRP). FXS is the most common monogenic cause of intellectual disability. There are two known mammalian paralogs of FMRP, FXR1P, and FXR2P. The functions of FXR1P and FXR2P and their possible roles in producing or modulating the phenotype observed in FXS are yet to be identified. Previous studies have revealed that mice lacking Fxr2 display similar behavioral abnormalities as Fmr1 knockout (KO) mice. In this study, we expand upon the behavioral phenotypes of Fmr1 KO and Fxr2(+/−) (Het) mice and compare them with Fmr1 KO/Fxr2 Het mice. We find that Fmr1 KO and Fmr1 KO/Fxr2 Het mice are similarly hyperactive compared to WT and Fxr2 Het mice. Fmr1 KO/Fxr2 Het mice have more severe learning and memory impairments than Fmr1 KO mice. Fmr1 KO mice display significantly impaired social behaviors compared to WT mice, which are paradoxically reversed in Fmr1 KO/Fxr2 Het mice. These results highlight the important functional consequences of loss or reduction of FMRP and FXR2P.